Drought Prone Area Programme Draft Annual Plan 1983-84 and 1984-85 Rajasthan - Planning Commission (Planning Commission, 1983)
Drought Prone Area Programme is one of the special programmes launched by the Government of India, in the State from the year 1974-75. This programme was started in 79 blocks of 13 districts, covering the desert as well as hilly regions with the object to obtain optimum returns per unit of primary resources namely land, water, live-stock and manpower to increase and stabilise the incomes of weaker sections and to minimise the impact of drought on agriculture production and income of the weaker sections. It was also thought to reduce the dependence on land and provide infrastructure for development of dairy, sheep and ground water exploitation. Since the beginning of the programme expenditure Incurred up to 1979-80 was of Rs. 4917.00 lacs.
Special Schemes Organisation Government of Rajasthan
Special Schemes Organisation Government of Rajasthan